2016
DOI: 10.1155/2016/4608979
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Ramipril and Candesartan against Myocardial Ischemic Reperfusion Injury: A Biochemical and Transmission Electron Microscopical Study

Abstract: The present study was designed to investigate the role of combined administration of Ramipril and Candesartan against in vitro myocardial ischemic reperfusion injury in rat. Male Wistar albino rats were divided into five groups (n = 6) and treated with saline (10 mL/kg), Ramipril (2 mg/kg), Candesartan (1 mg/kg), and the combination of both drugs, respectively 24 h before induction of global ischemia (5 min of stabilization, 9 min of global ischemia, and 12 min of reflow). Combination of Ramipril and Candesart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Our findings are in accordance with a previous study where Ram showed antioxidant effects in rats with myocardial ischemia/reperfusion injury. 78 The antioxidant effects of Ram could be explained by the fact that angiotensin II is known to induce oxidative stress. 77,79 The hearts of Ram-treated rats showed a significant reduction in the levels of the proapoptotic proteins Bax and caspase-3.…”
Section: Papermentioning
confidence: 99%
“…Our findings are in accordance with a previous study where Ram showed antioxidant effects in rats with myocardial ischemia/reperfusion injury. 78 The antioxidant effects of Ram could be explained by the fact that angiotensin II is known to induce oxidative stress. 77,79 The hearts of Ram-treated rats showed a significant reduction in the levels of the proapoptotic proteins Bax and caspase-3.…”
Section: Papermentioning
confidence: 99%
“…Furthermore, the progression of AH leads to the depletion of the compensatory mechanisms, and they can no longer reduce the discrepancy between the enlarged cardiac volume and the decreased CD [13,52]. Moreover, with time this adaptive hypertrophy advances to HF, which can be explained by structural damage to the membranes of the cardiomyocytes due to physical overstretching on the one hand and in response to reactive oxygen radicals, pathological cytokines and endothelial damage [3,44]. Despite vigorous research in the last few decades, the etiology of hypertension is not yet completely known.…”
Section: Role Of Vegf In Cardiac and Renal Pathologymentioning
confidence: 99%
“…ARBs have many cardiovascular and pleiotropic effects making them widely used in clinical practice ( Chrysant and Chrysant, 2006 ). Candesartan, a potent ARB with a long duration of action, has shown to be effective in several models of ischemia–reperfusion ( Culman et al, 2017 , Sheik Uduman et al, 2016 , Takagi et al, 2006 ). Interestingly, candesartan was found to exert a direct modulatory effect on the ACE 2/ Ang (1–7)/ Mas-1 receptor axis in addition to its well-known AT1 receptor blocking property ( Arumugam et al, 2012 , Pernomian et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%